Anandamide down-regulates placental transporter expression through CB2 receptor-mediated inhibition of cAMP synthesis. (March 2019) - Szilagyi, John T.; Composto-Wahler, Gabriella M.; Joseph, Laurie B.; Wang, Bingbing; Rosen, Todd; Laskin, Jeffrey D.; Aleksunes, Lauren M.
Abstract: The BCRP/ABCG2 efflux transporter is expressed on the membrane of placental syncytiotrophoblasts and protects the fetus from toxicant exposure. Syncytiotrophoblasts arise from the fusion of cytotrophoblasts, a process negatively regulated by the endocannabinoid, anandamide (AEA). It is unknown whether AEA can influence fetal concentrations of xenobiotics by modulating the expression of transporters in syncytiotrophoblasts. Here, we sought to characterize and identify the mechanism(s) responsible for AEA-mediated down-regulation of the BCRP transporter in human placental explants and BeWo trophoblasts. Treatment of human placental explants with AEA (1 μM, 24 h) reduced hCGα, syncytin-1, and BCRP mRNAs by ˜30%. Similarly, treatment of BeWo trophoblasts with AEA (0–10 μM, 3-24 h) coordinately down-regulated mRNAs for hCGß, syncytin-2, and BCRP. In turn, AEA increased the sensitivity of trophoblasts to the cytotoxicity of mitoxantrone, a known BCRP substrate, and environmental and dietary contaminants including mycoestrogens and perfluorinated chemicals. AEA-treated trophoblasts also demonstrated reduced BCRP transport of the mycoestrogen zearalenone and the diabetes drug glyburide, labeled with BODIPY. The AEA-mediated reduction of BCRP mRNA was abrogated when placental cells were co-treated with AM630, a CB2 receptor inhibitor, or 8-Br-cAMP, a cAMP analog. AEA reduced intracellular cAMP levels in trophoblasts by 75% at 1 h, and completely inhibited forskolin-induced phosphorylation of the cAMP response element binding protein (CREB). AEA also decreased p-CREB binding to the BCRP promoter. Taken together, our data indicate that AEA down-regulates placental transporter expression and activity via CB2-cAMP signaling. This novel mechanism may explain the repression of placental BCRP expression observed during diseases of pregnancy.